The Incidence of Audible Steam Pops Is Increased and Unpredictable With the ThermoCool® Surround Flow Catheter During Left Atrial Catheter Ablation: A Prospective Observational Study. (27th July 2015) - THEIS, CATHRIN; ROSTOCK, THOMAS; MOLLNAU, HANKE; SONNENSCHEIN, SEBASTIAN; HIMMRICH, EWALD; KÄMPFNER, DENISE; OCETE, BLANCA QUESADA; BOCK, KARSTEN; MÜNZEL, THOMAS; KONRAD, TORSTEN
Audible Steam Pops During Left Atrial Catheter Ablation Introduction Open irrigated radiofrequency (RF) ablation catheters with a porous tip (56 holes, TC‐SF) permit delivering RF energy in a temperature‐controlled mode without temperature rise. This prospective observational study investigated the association of different catheter parameters on the occurrence of audible steam pops during left atrial (LA) ablation. Methods and Results A total of 226 patients underwent TC‐SF catheter ablation for atrial fibrillation. RF power delivery, impedance and catheter tip temperature were continually recorded throughout the ablation. Pulmonary vein isolation was performed with a maximum of 27 W and LA electrogram‐guided or linear ablation with a maximum of 30 W. A total of 59 audible steam pops occurred, 2 of them resulting in pericardial tamponade. In the initial 89 patients, with an irrigation flow rate of 10 mL/min, 18 steam pops with one tamponade occurred in 12 (14%) patients. Subsequently, the irrigation flow rate was increased to 20 mL/min in the following 137 patients, resulting in the occurrence of 41 steam pops including one case of tamponade in a total of 30 (22%) patients. The maximal power was significantly higher in RF applications associated with a pop than those that did not. In only 12 (20%) steam pops, a significant impedance change occurred immediately before pop occurrence (4 [7%] impedance rise >10 ohm, 8 [13%] impedance drop >15 ohm). Conclusions The TC‐SF catheter does not provide sufficient feedback from the ablated tissue to prevent steam popping.